PERAN ORANG TUA DALAM MEMBENTUK KARAKTER DISIPLIN ANAK DI DUSUN KLEREK DESA TORONGREJO KECAMATAN JUNREJO KOTA BATU - Tya Yusrani Prantika; Muhammad Sulistiono; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This article discusses how the planning, implementation of parents in shaping the character of children's discipline. The research was conducted in Klerek Hamlet, Torongrejo Village, Junrejo District, Batu City, using interview, observation and documentation methods. The results of this study obtained about planning in shaping the character of children, namely improving the morals of parents first, paying attention to the development of the character of children's discipline, establishing good communication with children, parents being consistent with the discipline that has been set. The implementation is getting children to respect time, using exemplary methods, giving advice to children, teaching children about good morals, getting children to obey the applicable rules. The supporting factors are the environment and teachers. Inhibiting factors are promiscuity, gadget technology, and lack of communication between parents and children.Keywords: Role of Parents, Children's Character, Discipline